Out-of-pocket health expenditure in sub Saharan Africa: The role of government and external health expenditures - Tewa Papy Voto; Nicholas Ngepah (Economies, 2025)
This study aims to analyze the impact of government and external health spending on OOPHE across 30 SSA countries from 1995 to 2021. Using advanced econometric techniques, including the cross-sectionally augmented autoregressive distributed Lags (CS-ARDL) model and the dynamic common correlated effects (DCCE) approach, the study examined both short-term and long-term effects. Findings reveal that in the long term, government health expenditure (GHE) has a more significant impact on reducing OOPHE compared to external health expenditure (EHE). However, in the short term, GHE initially increases OOPHE, while EHE directly reduces it. This suggests that increasing GHE is more effective for long-term progress towards SDG 3. In contrast, EHE can provide immediate relief in the short term. To achieve SDG 3, policymakers should focus on increasing GHE for sustained improvements while leveraging EHE to address short-term challenges. Combining both strategies can optimize progress toward ensuring universal health coverage and well-being for all.
Keywords: 330; OOPHE; GHE; EHE; CS-ARDL; DCCE